2013
DOI: 10.3892/etm.2013.1462
|View full text |Cite
|
Sign up to set email alerts
|

Contradictory imaging and EEG results in resection surgery of bitemporal lobe epilepsy: A case report

Abstract: The present study describes the case of a 27-year-old, right-handed female with bilateral mesial temporal lobe epilepsy. Electroencephalogram (EEG) monitoring from implanted electrodes displayed two different and independent onsets on the two sides of the mesial temporal structures, which specifically included clinical generalized tonic clonic seizure (GTCS) discharges originating from the left mesial temporal lobe, as well as complex partial seizure (CPS) discharges arising from the right mesial region. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Except for points 1 and 2, which have never been reported before, these findings are in agreement with those of earlier studies [11,14,36]. Moreover, histopathology showed that only two of our four surgically treated BTLE patients had FCD, and other studies have found that the main histological finding in BTLE is HS [8,37], and have only infrequently described FCD or other focal lesions. All of these data indicate that the etiologies commonly observed in UTLE patients are less probable, or at least differently expressed, in patients with BTLE, thus leading to a distinct anatomo-electroclinical phenotype.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Except for points 1 and 2, which have never been reported before, these findings are in agreement with those of earlier studies [11,14,36]. Moreover, histopathology showed that only two of our four surgically treated BTLE patients had FCD, and other studies have found that the main histological finding in BTLE is HS [8,37], and have only infrequently described FCD or other focal lesions. All of these data indicate that the etiologies commonly observed in UTLE patients are less probable, or at least differently expressed, in patients with BTLE, thus leading to a distinct anatomo-electroclinical phenotype.…”
Section: Discussionsupporting
confidence: 94%
“…Some have indicated good surgical outcomes [8,10,12,40], but others have found unfavourable outcomes [9,11,14,41] and even a worsening after surgery [37]. On the basis of the data relating to our few patients who underwent surgery, patients with BTLE are not good candidates for resection, and probably account for a large proportion of poor TLE surgery outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…The EEG method of prognosis used in this study agrees with previous reports on use of the corneal nerve for disease diagnosis and prognosis [ 13 15 ]. However, using EEG to diagnose corneal nerve injury in retinoblastoma patients has not been explored in previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Epilepsy is a chronic neurological disorder caused by the repeated and excessive abnormal electrical impulses of brain neurons (1). The prevalence of epilepsy in the global population is ~5%, with up to 10 million patients with epilepsy in China alone (15).…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is a neurological disease, and usually refers to a chronic disease with various recurrent clinical manifestations, resulting from the sudden abnormal electrical impulses of neurons in the brain (1). Refractory epilepsy, also known as intractable epilepsy, refers to epilepsy occurring multiple times each month and persists for >2 years, with no improvement observed with regular treatment (2).…”
Section: Introductionmentioning
confidence: 99%